Ischaemic Oculomotor Nerve Palsy Isolated to the Levator: A Case Report - Tooley, Andrea A. (Neuroophthalmology, 2018)
Ischaemic oculomotor nerve (CN III) palsies frequently present with abrupt onset ptosis, ophthalmoplegia, diplopia, ipsilateral pain, and little to no anisocoria. An isolated microvascular ischaemic insult to the superior division of CN III is uncommon, and usually affects both the superior rectus and levator muscles. We present a rare case of an ischaemic CN III palsy isolated to the levator palpebrae superioris muscle only. Although rare, microvascular ischaemic CN III palsies should be on the differential of isolated ptosis. Other causes of isolated ptosis, such as myasthenia gravis or an orbital lesion, should be excluded.